Polyion liquid-porous carbon composite material, preparation and application thereof in catalyzing conversion of low-concentration carbon dioxide

By using polyionic liquid-porous carbon composite materials as catalysts, the problem of separation and recycling of existing catalysts in the reaction of CO2 and epoxide is solved, and efficient catalysis and good cycle performance under mild conditions are achieved.

CN119327511APending Publication Date: 2025-01-21QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411368917.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the catalytic cycloaddition reaction between CO2 and epoxide, the existing catalysts have problems such as complicated separation steps between the catalyst and the product, the catalyst is not easy to recycle, the active components are easily lost, and the reaction conditions are harsh.

Method used

Polyionic liquid-porous carbon composite materials are used as catalysts, and Lewis acid-base site-modified porous carbon materials are combined with polyionic liquids through specific preparation steps to form composite materials with high-density active sites for catalyzing low concentrations. Cycaddition reaction of CO2 with epoxides.

Benefits of technology

It has achieved efficient catalytic conversion of low-concentration CO2 into cyclic carbonates under mild, solvent-free, and additive-free conditions. The catalyst has excellent recycling performance and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a polyion liquid-porous carbon composite material, preparation thereof and application of the polyion liquid-porous carbon composite material in catalyzing conversion of low-concentration carbon dioxide. According to the preparation method, a novel Lewis acid-base active site and nucleophilic group co-modified polyion liquid-porous carbon composite material is prepared by combining pyrolysis of a liquid organic precursor with an in-situ polymerization strategy; the material is used as a catalyst, epoxide and low-concentration carbon dioxide are used as reactants, and high-selectivity synthesis of the cyclic carbonate is realized under the conditions that the dosage of the catalyst is 4%-8% of the mass percent of the epoxide, the reaction pressure is 0.5-2.5 MPa, the reaction temperature is 70-110 DEG C and the reaction time is 8-16 hours. The catalyst is easy to separate after the reaction is finished, and the catalyst is excellent in recycling performance. The method using the composite material provided by the invention as the catalyst for the cycloaddition reaction of carbon dioxide and epoxide overcomes the defects of low activity, poor stability, difficulty in recycling and the like of the currently reported catalyst, and has good industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional material preparation and catalysis, and specifically relates to a polyionic liquid-porous carbon composite material and its application in preparation and catalysis of low-concentration carbon dioxide conversion. Background Art

[0002] Due to the extensive use of fossil fuels by humans, carbon dioxide (CO2) emissions have increased year by year, leading to a series of frequent environmental problems, such as greenhouse effect, global warming, and sea level rise. Therefore, CO2 emission reduction is imperative. While CO2 poses a threat and damage to human society and the ecological environment, it is also an important non-toxic, low-cost, and renewable C1 resource in industry. With the rapid development of catalytic technology, the chemical resource utilization of CO2 has shown increasingly important scientific and economic value, which meets the needs of effectively controlling carbon emissions and is of great significance from the perspective of environmental protection and sustainable development. Since CO2 has thermodynamic stability and kinetic inertness, the realization of the resource utilization of CO2 requires the development of effective catalytic technology. It is reported that the resource utilization rate of CO2 in industrial production currently accounts for only 0.36% of the total global emissions. Therefore, there is still a lot of room for development in the chemical resource utilization of CO2.

[0003] Among them, the coupling of CO2 and epoxide to prepare cyclic carbonates is one of the ways with industrial prospects for large-scale resource utilization of CO2. The reaction is shown in Formula I and has attracted widespread attention.

[0004] Formula I On the one hand, this reaction route conforms to atom economy and can replace the traditional toxic phosgene process to meet the development requirements of green chemistry; on the other hand, the product cyclic carbonate has excellent physical and chemical properties, such as high boiling point, high polarity, low volatility, good biodegradability and solubility, and is widely used in green aprotic solvents, lithium-ion battery electrolytes, additives, plastics, pharmaceuticals and fine chemical intermediates.

[0005] For the cycloaddition reaction of CO2 and epoxides, a variety of catalysts have been reported at home and abroad. Among them, homogeneous catalysts include alkali metal salts, organic bases, metal complexes, ionic liquids, etc., but there are problems such as cumbersome separation steps between catalysts and products and difficulty in recycling catalysts; heterogeneous catalysts include polyionic liquids, porous organic polymers, metal organic frameworks, metal oxides, mesoporous organosilicon, etc. Although they overcome the disadvantages of homogeneous catalysts and products that are difficult to separate, they still have defects such as easy loss of active components of catalysts, low catalytic activity leading to harsh reaction conditions (high temperature and high pressure) or dependence on homogeneous co-catalysts that are difficult to separate. Therefore, it has become an inevitable development trend to develop efficient catalysts that are stable in structure, easy to separate and reuse, and can catalyze the cycloaddition reaction of CO2 and epoxides under mild conditions.

[0006] Porous carbon materials have advantages such as high specific surface area, excellent porous structure, controllable chemical composition and synthetic diversity, which makes them more competitive in optimizing CO2 adsorption capacity and improving CO2 conversion efficiency. Vidal et al. (ChemCatChem, 2019, 11(16): 4089-4095.) used biomass materials such as hardwood (forestry, pulp and papermaking residues) and softwood (birch and pine sawdust, etc.) as precursors and obtained porous carbon materials containing -COOH (ox-bc hw ). hw As a catalyst, tetrabutylammonium bromide (TBAB) as a co-catalyst, the cycloaddition reaction of CO2 and epichlorohydrin was catalyzed at 110℃, 1 MPa, and 6h. The yield of cyclochloropropylene carbonate was 97.1%. hwThe introduction of homogeneous co-catalysts that are not easy to separate is still required for catalytic cycloaddition reactions, which does not meet the needs of green development. In order to avoid the use of co-catalysts, Samikannu et al. (Applied Catalysis B: Environmental, 2019, 241: 41-51.) used cheap and readily available nitrogen-rich biomass as a precursor to prepare nitrogen-doped porous carbon materials (MA500), and catalyzed the cycloaddition reaction of CO2 and epoxides under solvent-free and co-catalyst-free conditions (150°C, 15 bar, 15 h), and the conversion rate and selectivity of cyclochloropropylene carbonate reached 99%. Although the problem of using co-catalysts has been solved, the reaction conditions are harsh and require more energy. In addition, most current studies use high-purity CO2 as a reactant for catalytic conversion, and the purification of CO2 requires multiple high-energy-consuming operations such as absorption, desorption, compression, and transportation, which is not conducive to sustainable development. Therefore, it is of great practical significance to design and develop new multifunctional carbon materials with both high activity and high stability to achieve efficient catalytic conversion of low-concentration CO2 under mild, solvent-free, and co-catalyst-free conditions. This application is a new technical solution explored based on the above research and development background. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a polyionic liquid-porous carbon composite material and its application in preparation and catalysis of low-concentration carbon dioxide conversion.

[0008] To solve the above problems, the technical solution adopted by the present invention is: Technical Theme 1 A polyionic liquid-porous carbon composite material, the preparation steps of which are as follows: S1: Mix melamine, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt and zinc acetate dihydrate in proportion at room temperature, and stir at room temperature for 8-12 hours to obtain a liquid organic precursor; S2: thermally decompose the liquid organic precursor at 600-700° C. in an inert gas atmosphere for 2-3 hours, and obtain a Lewis acid-base site-modified porous carbon material through post-treatment; S3: dissolving 1,4-dibromobutane and 1-vinylimidazole in a hydrothermal reactor filled with tetrahydrofuran at a molar ratio of 1:2-2.5, stirring until uniformly mixed at room temperature, reacting at 80-100° C. for 18-24 hours, and after the reaction is completed, post-treating to obtain a white solid 1,4-di(3-vinylimidazole)butane dibromide; S4: The porous carbon material modified with Lewis acid-base sites obtained in S2 is placed in a reaction bottle filled with anhydrous ethanol, subjected to ultrasonic treatment to make it evenly dispersed, and then the 1,4-di(3-vinylimidazole)butane dibromide, p-divinylbenzene and 2,2'-azobisisobutyronitrile obtained in S3 are dissolved in anhydrous ethanol in proportion, and added to the anhydrous ethanol solution of the porous carbon material modified with Lewis acid-base sites under stirring, and the mixed solution is reacted at 70-90°C under a nitrogen atmosphere for 16-24 hours, and a polyionic liquid-porous carbon composite material having Lewis acid-base active sites and nucleophilic groups is obtained through post-treatment.

[0009] As some preferred embodiments of the present invention, the molar ratio of melamine, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and zinc acetate dihydrate in S1 is 1:1:10-15:1-1.3; In S4, the mass ratio of the Lewis acid-base site modified porous carbon material to p-divinylbenzene is 1:0.6-1, and the molar ratio of p-divinylbenzene to 2,2'-azobisisobutyronitrile is 5-15:10:3.

[0010] As some preferred embodiments of the present invention, the molar ratio of melamine, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and zinc acetate dihydrate in S1 is 1:1:13:1.14; The mass ratio of the Lewis acid-base site modified porous carbon material to p-divinylbenzene in the S4 is 1:0.8, and the molar ratio of 1,4-di(3-vinylimidazole)butane dibromide, p-divinylbenzene and 2,2'-azobisisobutyronitrile is 10:10:3.

[0011] As some preferred embodiments of the present invention, the pyrolysis reaction temperature in S2 is 700° C., and the pyrolysis reaction time is 2 hours; The heating reaction condition of the mixture in S3 is 90°C for 20 hours; The mixed solution in S4 was heated to react under a nitrogen atmosphere at a temperature of 80° C. for 24 hours.

[0012] As some preferred embodiments of the present invention, the post-treatment in S2 is to naturally cool to room temperature, wash with deionized water, N,N-dimethylformamide and methanol respectively, and then filter, and vacuum dry the solid to obtain a porous carbon material modified with Lewis acid and base sites; The post-treatment in S3 is to naturally cool to room temperature, and the obtained white solid is filtered, washed with ethyl acetate, and vacuum dried to obtain 1,4-di(3-vinylimidazole)butane dibromide; The post-treatment in S4 is to naturally cool the temperature to room temperature, and the obtained solid is filtered, washed with anhydrous ethanol, and vacuum dried to obtain a polyionic liquid-porous carbon composite material.

[0013] Technical Theme 2 A method for preparing a polyionic liquid-porous carbon composite material as described in technical subject one.

[0014] Technical Theme 3 A use of the polyionic liquid-porous carbon composite material as described in the first technical subject as a catalyst for the cycloaddition reaction of low-concentration carbon dioxide and epoxide.

[0015] Technical Theme 4 A method for preparing cyclic carbonate by coupling low-concentration carbon dioxide with epoxide catalyzed by a polyionic liquid-porous carbon composite material as described in the first technical theme: using the polyionic liquid-porous carbon composite material as a catalyst, low-concentration carbon dioxide and epoxide are reacted through a cycloaddition reaction to synthesize cyclic carbonate.

[0016] As some preferred embodiments of the present invention, the volume concentration of the low-concentration carbon dioxide is 10%-25%; The epoxide structural formula is as follows: ; The dosage of the polyionic liquid-porous carbon composite material catalyst is 4%-8% of the mass of the epoxide; the cycloaddition reaction temperature is 70-110° C., the reaction pressure is 0.5-2.5 MPa, and the reaction time is 8-16 hours.

[0017] As some preferred embodiments of the present invention, the volume concentration of the low-concentration carbon dioxide is 15%; The cycloaddition reaction temperature is 100° C., the reaction pressure is 1 MPa, and the reaction time is 13 hours.

[0018] The beneficial effects of adopting the above technical solution are: 1. The novel polyionic liquid-porous carbon composite material provided in the present application integrates multiple high-density active sites, including Lewis acid, Lewis base and nucleophilic groups, and has the function of simultaneously and efficiently activating epoxides and CO2, so that the invented polyionic liquid-porous carbon composite material can catalyze the conversion of low-concentration CO2 into cyclic carbonates under mild, solvent-free and catalyst-free conditions.

[0019] 2. The method provided in the present application for preparing cyclic carbonates by catalyzing the coupling of low-concentration CO2 and epoxide by a polyionic liquid-porous carbon composite material. The catalyst can be separated by simple filtration, and the catalytic activity does not decrease significantly after being recycled for 5 times, showing excellent recycling performance and structural stability.

[0020] 3. The technology of this application overcomes the shortcomings of currently reported catalysts, such as low catalytic activity, poor stability, and difficulty in recycling, and has good potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the preparation of the polyionic liquid-porous carbon composite material of the present invention; Figure 2 The polyionic liquid-porous carbon composite material PIL-Br prepared in Example 3 of the present invention 1.0 @Zn-CTM solid state NMR carbon spectrum; Figure 3 The fresh PIL-Br prepared in Example 3 of the present invention 1.0 @Zn-CTM composite material and recovery PIL-Br after the reaction of application example 17 1.0 @Structural characterization comparison diagram of Zn-CTM composite materials, where (a) is the infrared spectra of the two materials; (b) is the thermogravimetric analysis spectra of the two materials; (c) is the nitrogen adsorption-desorption isotherms of the two materials; and (d) is the pore size distribution diagram of the two materials. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] In this specific embodiment, the polyionic liquid-porous carbon composite material PIL-Br X The preparation diagram of @Zn-CTM (X=0.5-1.5) is shown in Figure 1 , wherein Zn-TM is a porous carbon material modified with Lewis acid-base sites before calcination, Zn-CTM is a porous carbon material modified with Lewis acid-base sites after calcination, IL is an ionic liquid, and X represents the molar ratio of 1,4-di(3-vinylimidazole)butane dibromide to p-divinylbenzene used in preparing the material.

[0024] Example 1 Preparation of Lewis acid-base site modified porous carbon materials (Zn-CTM) (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1.14 mmol, 0.25 g) were uniformly mixed in 13 mmol ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 700 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and cooled naturally to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material with a specific surface area of ​​622 m 2 / g, expressed as Zn-CTM.

[0025] Example 2 Preparation of 1,4-bis(3-vinylimidazole)butane dibromide (C4ImBr) 1,4-di(3-vinylimidazole)butane dibromide (C4ImBr) was prepared by solvothermal method in a hydrothermal reactor lined with polytetrafluoroethylene. The specific process is as follows: 1,4-dibromobutane (13.3 mmol, 2.87 g) and 1-vinylimidazole (26.6 mmol, 2.5 g) were dissolved in a hydrothermal reactor containing 5 mL of tetrahydrofuran (THF). Stirred for 1 h at room temperature, the mixture was reacted at 90 °C for 20 h. After cooling to room temperature, the crude product was filtered and separated, washed with ethyl acetate (30 mL×3), and vacuum dried at 80 °C for 12 h to obtain a white solid C4ImBr (yield: 80%); Example 3 Polyionic Liquid-Porous Carbon Composites PIL-Br 1.0 Preparation of @Zn-CTM Weigh 0.16 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonicate for 10 min to evenly disperse Zn-CTM. Then weigh C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. Heat the mixed solution to 80°C and react under N2 conditions for 24 h. The color of the solution changes from black to gray. After the reaction is completed, filter and separate the solid, wash it with anhydrous ethanol (30 mL×3), and vacuum dry it at 80°C for 12 h to obtain PIL-Br. 1.0 @Zn-CTM, yield 95%.

[0026] Figure 2 PIL-Br 1.0 The solid NMR carbon spectrum of @Zn-CTM clearly showed the signal peaks of all carbon atoms, proving that DVB and C4ImBr polymerized and successfully composited with the porous carbon material.

[0027] Example 4 Polyionic Liquid-Porous Carbon Composites PIL-Br 0.5 Preparation of @Zn-CTM Weigh 0.16 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonicate for 10 min to evenly disperse Zn-CTM. Then weigh C4ImBr (0.5 mmol, 0.20 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. Heat the mixed solution to 80°C and react under N2 for 24 h. The color of the solution changes from black to gray. After the reaction is completed, filter and separate the solid, wash it with anhydrous ethanol (30 mL×3), and vacuum dry it at 80°C for 12 h to obtain PIL-Br. 0.5 @Zn-CTM, yield 97%.

[0028] Example 5 Polyionic Liquid-Porous Carbon Composites PIL-Br 1.5 Preparation of @Zn-CTM materials Weigh 0.16 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonicate for 10 min to evenly disperse Zn-CTM. Then weigh C4ImBr (1.5 mmol, 0.60 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. Heat the mixed solution to 80°C and react under N2 conditions for 24 h. The color of the solution changes from black to gray. After the reaction is completed, filter and separate the solid, wash it with anhydrous ethanol (30 mL×3), and vacuum dry it at 80°C for 12 h to obtain PIL-Br. 1.5 @Zn-CTM, yield 94%.

[0029] Example 6 0.13 g of Zn-CTM prepared in Example 1 was weighed and added to a round-bottom flask containing 10 mL of anhydrous ethanol, and ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1.0 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h, and the color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0030] Example 7 Weigh 0.22 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment is performed for 10 min to uniformly disperse Zn-CTM. Then weigh C4ImBr (1.0 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution is heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changes from black to gray. After the reaction is completed, the solid is separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0031] Example 8 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1 mmol, 0.22 g) were uniformly mixed in 10 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor. (2) The liquid organic precursor was transferred to a porcelain boat and heated to 700 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0032] (3) Weigh 0.16 g of Zn-CTM prepared in Example 8 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the stirred anhydrous ethanol solution containing Zn-CTM. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0033] Example 9 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1.3 mmol, 0.28 g) were uniformly mixed in 15 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 700 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0034] (3) Weigh 0.16 g of Zn-CTM prepared in Example 9 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the stirred anhydrous ethanol solution containing Zn-CTM. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0035] Example 10 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1.14 mmol, 0.25 g) were uniformly mixed in 13 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 600 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 3 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0036] (3) Weigh 0.16 g of Zn-CTM prepared in Example 10 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the stirred anhydrous ethanol solution containing Zn-CTM. The mixed solution was heated to 90°C and reacted under N2 conditions for 16 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0037] Embodiment 11 Weigh 0.16 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution was heated to 70°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0038] Comparative Example 1 Weigh C4ImBr (1 mmol, 0.40 g) prepared in Example 2, p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) respectively and dissolve them in 10 mL of anhydrous ethanol. Heat the mixed solution to 80°C and react under N2 for 24 h. After the reaction, filter and separate the solid, wash it with anhydrous ethanol (30 mL×3), and vacuum dry it at 80°C for 12 h to obtain PIL-Br. 1.0 .

[0039] Comparative Example 2 (1) 2,6-Diaminopyridine (0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1.14 mmol, 0.25 g) were uniformly mixed in 13 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 700 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0040] (3) Weigh 0.16 g of Zn-CTM prepared in Comparative Example 2 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution containing Zn-CTM under stirring. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0041] Comparative Example 3 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (0.57 mmol, 0.12 g) were uniformly mixed in 13 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 700 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0042] (3) Weigh 0.16 g of Zn-CTM prepared in Comparative Example 3 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the stirred anhydrous ethanol solution containing Zn-CTM. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0043] Comparative Example 4 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (2.28 mmol, 0.50 g) were uniformly mixed in 13 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 700 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0044] (3) Weigh 0.16 g of Zn-CTM prepared in Comparative Example 4 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution containing Zn-CTM under stirring. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0045] Comparative Example 5 Weigh 0.10 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment is performed for 10 min to uniformly disperse Zn-CTM. Then weigh C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution is heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changes from black to gray. After the reaction is completed, the solid is separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0046] Comparative Example 6 Weigh 0.30 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment is performed for 10 min to uniformly disperse Zn-CTM. Then weigh C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution is heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changes from black to gray. After the reaction is completed, the solid is separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0047] Comparative Example 7 0.16 g of Zn-CTM prepared in Example 1 was weighed and added to a round-bottom flask containing 10 mL of anhydrous ethanol, and ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.03 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h, and the color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0048] Comparative Example 8 0.16 g of Zn-CTM prepared in Example 1 was weighed and added to a round-bottom flask containing 10 mL of anhydrous ethanol, and ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.10 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution with Zn-CTM under stirring. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h, and the color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration, washed with anhydrous ethanol (30 mL×3), and vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0049] Comparative Example 9 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1.14 mmol, 0.25 g) were uniformly mixed in 13 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 800 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0050] (3) Weigh 0.16 g of Zn-CTM prepared in Comparative Example 9 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse the Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the anhydrous ethanol solution containing Zn-CTM under stirring. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0051] Comparative Example 10 (1) Melamine (MEL, 1.0 mmol, 0.13 g), 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine (TFPT, 1.0 mmol, 0.44 g) and Zn(OAc)2∙2H2O (1.14 mmol, 0.25 g) were uniformly mixed in 13 mmol ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([Bmim][NTf2]) and stirred at room temperature for 12 h to obtain a uniform liquid organic precursor; (2) The liquid organic precursor was transferred to a porcelain boat and heated to 500 °C in a tube furnace at a heating rate of 5 °C / min under a nitrogen atmosphere. The mixture was kept at this temperature for 2 h and naturally cooled to room temperature to obtain a black solid. The solid was washed with 30 mL of deionized water, 30 mL of N,N-dimethylformamide and 30 mL of methanol in sequence and then filtered. The solid was dried at 80 °C under vacuum for 12 h to obtain a Zn / N co-doped porous carbon material, denoted by Zn-CTM.

[0052] (3) Weigh 0.16 g of Zn-CTM prepared in Comparative Example 10 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 min to uniformly disperse Zn-CTM. Then, C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 were weighed and dissolved in 10 mL of anhydrous ethanol, and then added to the stirred anhydrous ethanol solution containing Zn-CTM. The mixed solution was heated to 80°C and reacted under N2 conditions for 24 h. The color of the solution changed from black to gray. After the reaction was completed, the solid was separated by filtration and washed with anhydrous ethanol (30 mL×3). It was vacuum dried at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0053] Comparative Example 11 Weigh 0.16 g of Zn-CTM prepared in Example 1 and add it to a round-bottom flask containing 10 mL of anhydrous ethanol, and ultrasonically treat it for 10 min to evenly disperse Zn-CTM. Then weigh C4ImBr (1 mmol, 0.40 g), p-divinylbenzene (DVB, 1 mmol, 0.13 g) and 2,2'-azobisisobutyronitrile (AIBN, 0.05 g) prepared in Example 2 and dissolve them in 10 mL of anhydrous ethanol, and then add them to the anhydrous ethanol solution with Zn-CTM under stirring. Heat the mixed solution to 70°C and react for 12 h under N2 conditions. After the reaction is completed, filter and separate the solid, wash it with anhydrous ethanol (30 mL×3), and vacuum dry it at 80°C for 12 h to obtain a polyionic liquid-porous carbon composite material.

[0054] Application Example 1 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 3 1.0 @Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 1.0 @Zn-CTM is 0.032g, accounting for 7.0% of the mass content of the reactants; low concentration carbon dioxide (15% CO2, 85% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 70°C, low concentration carbon dioxide is introduced to keep the pressure constant at 2.0MPa, and the reaction is continued for 15h; after the reaction is completed, the reactor is cooled to room temperature in an ice water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 86%, and the selectivity is ≥99%.

[0055] Application Example 2 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 3 1.0 @Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 1.0 @Zn-CTM is 0.03g, accounting for 6.5% of the mass content of the reactants; low concentration carbon dioxide (15% CO2, 85% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 100°C, low concentration carbon dioxide is introduced to keep the pressure constant at 1.0MPa, and the reaction is continued for 13h; after the reaction is completed, the reactor is cooled to room temperature in an ice water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 94%, and the selectivity is ≥99%.

[0056] Application Example 3 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 3 1.0 @Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 1.0 @Zn-CTM is 0.019g, accounting for 4.0% of the mass content of the reactants; low concentration carbon dioxide (15% CO2, 85% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 110°C, low concentration carbon dioxide is introduced to keep the pressure constant at 0.5MPa, and the reaction is continued for 16h; after the reaction is completed, the reactor is cooled to room temperature in an ice water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 95%, and the selectivity is ≥99%.

[0057] Application Example 4 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 4 0.5 @Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 0.5 @Zn-CTM is 0.037g, accounting for 8.0% of the mass content of the reactants; low-concentration carbon dioxide (25% CO2, 75% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 100°C, low-concentration carbon dioxide is introduced to maintain a constant pressure of 1.5MPa, and the reaction is continued for 13h; after the reaction is completed, the reactor is cooled to room temperature in an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 87%, and the selectivity is ≥99%.

[0058] Application Example 5 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 5 1.5@Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 1.5 @Zn-CTM is 0.035g, accounting for 7.5% of the mass content of the reactants; low concentration carbon dioxide (10% CO2, 90% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 90°C, low concentration carbon dioxide is introduced to keep the pressure constant at 2.5MPa, and the reaction is continued for 12h; after the reaction is completed, the reactor is cooled to room temperature in an ice water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 89%, and the selectivity is ≥99%.

[0059] Application Example 6 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 3 1.0 @Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 1.0 @Zn-CTM is 0.03g, accounting for 6.5% of the mass content of the reactants; low concentration carbon dioxide (25% CO2, 75% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 90°C, low concentration carbon dioxide is introduced to keep the pressure constant at 1.0MPa, and the reaction is continued for 13h; after the reaction is completed, the reactor is cooled to room temperature in an ice water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 93%, and the selectivity is ≥99%.

[0060] Application Example 7 Take the reactant epichlorohydrin and the catalyst PIL-Br prepared in Example 3 1.0 @Zn-CTM was added into a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, including 5 mmol of epichlorohydrin, 5 mmol of PIL-Br 1.0 @Zn-CTM is 0.037g, accounting for 8.0% of the mass content of the reactants; low-concentration carbon dioxide (20% CO2, 80% N2) is slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath is heated to 100°C, low-concentration carbon dioxide is introduced to keep the pressure constant at 2.5MPa, and the reaction is continued for 8h; after the reaction is completed, the reactor is cooled to room temperature in an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 95%, and the selectivity is ≥99%.

[0061] Application Example 8 The reactant epichlorohydrin and the catalyst polyionic liquid-porous carbon composite material prepared in Example 6 were added in sequence to a 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein 5 mmol of epichlorohydrin and 0.03 g of polyionic liquid-porous carbon composite material were used, accounting for 6.5% of the mass content of the reactants; low-concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath was heated to 100°C, low-concentration carbon dioxide was introduced to keep the pressure constant at 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature in an ice-water bath, and the product was quantitatively analyzed by gas chromatography, and the yield of propylene carbonate was 92%, and the selectivity was ≥99%.

[0062] Application Example 9 The reactant epichlorohydrin and the catalyst polyionic liquid-porous carbon composite material prepared in Example 7 were added in sequence to a 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein 5 mmol of epichlorohydrin and 0.03 g of polyionic liquid-porous carbon composite material were used, accounting for 6.5% of the mass content of the reactants; low-concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath was heated to 100°C, low-concentration carbon dioxide was introduced to maintain a constant pressure of 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature in an ice-water bath, and the product was quantitatively analyzed by gas chromatography, and the yield of propylene carbonate was 88%, and the selectivity was ≥99%.

[0063] Application Example 10 The reactant epichlorohydrin and the catalyst polyionic liquid-porous carbon composite material prepared in Example 8 were added in sequence to a 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein 5 mmol of epichlorohydrin and 0.03 g of polyionic liquid-porous carbon composite material were used, accounting for 6.5% of the mass content of the reactants; low-concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to exclude the remaining air inside; then, the reactor oil bath was heated to 100°C, low-concentration carbon dioxide was introduced to maintain a constant pressure of 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature in an ice-water bath, and the product was quantitatively analyzed by gas chromatography, and the yield of propylene carbonate was 90%, and the selectivity was ≥99%.

[0064] Application Example 11 The reactant epichlorohydrin and the catalyst polyionic liquid-porous carbon composite material prepared in Example 9 were added in sequence to a 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein 5 mmol of epichlorohydrin and 0.03 g of polyionic liquid-porous carbon composite material were used, accounting for 6.5% of the mass content of the reactants; low-concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath was heated to 100°C, low-concentration carbon dioxide was introduced to maintain a constant pressure of 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature in an ice-water bath, and the product was quantitatively analyzed by gas chromatography, and the yield of propylene carbonate was 93%, and the selectivity was ≥99%.

[0065] Application Example 12 The specific experimental process and detection method are the same as those in Application Example 2, except that epichlorohydrin is replaced by other epoxides with different substituents, and the temperature and time are adjusted according to the changes in the epoxides, and cycloaddition reactions are carried out with low concentration carbon dioxide (15% CO2, 85% N2) respectively. The results are shown in Table 1.

[0066] Table 1 PIL-Br 1.0 @Zn-CTM catalyzed cycloaddition reactions of different epoxides with CO2 Application Examples 13-17 The specific experimental conditions and steps are the same as those in Application Example 2. After the reaction, PIL-Br is recovered by centrifugation. 1.0 @Zn-CTM catalyst, and after washing with ethyl acetate and vacuum drying, the recovered catalyst was used for 5 cycles under the same conditions. The results are shown in Table 2. In addition, the structure of the catalyst after 5 cycles was characterized. The results are shown in Table 2. Figure 3 As shown. By using fresh PIL-Br 1.0 @Zn-CTM catalyst structure was compared and it was found that the catalyst structure did not change significantly after recycling, which proved the excellent structural stability and recycling performance of the catalyst.

[0067] Table 2 Experimental results of catalyst recycling in Application Example 2 Application Comparative Example 1 The Zn-CTM prepared in Example 1 and the PIL-Br prepared in Comparative Example 1 were 1.0 Mix thoroughly, where PIL-Br 1.0 is 0.024 g, and Zn-CTM is 0.006 g.

[0068] Take the reactants epichlorohydrin and the Zn-CTM prepared in Example 1 and the PIL-Br prepared in Comparative Example 1 1.0 The above mixtures were added in sequence to a 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein 5 mmol of epichlorohydrin was used, accounting for 6.5% of the mass content of the reactants; low-concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to remove the remaining air inside; then, the reactor oil bath was heated to 100°C, low-concentration carbon dioxide was introduced to maintain a constant pressure of 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature with an ice-water bath, and the product was quantitatively analyzed by gas chromatography, with a yield of 71% for epichlorohydrin carbonate and a selectivity of ≥99%.

[0069] Application Comparative Example 2 The reactants epichlorohydrin and Zn-CTM prepared in Example 1 were added into a 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein 5 mmol of epichlorohydrin and 0.03 g of Zn-CTM accounted for 6.5% of the reactants by mass; low-concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to remove the remaining air inside; then, the reactor was heated to 100°C in an oil bath, low-concentration carbon dioxide was introduced to maintain a constant pressure of 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature in an ice-water bath, and the product was quantitatively analyzed by gas chromatography, and the yield of propylene carbonate was 32%, and the selectivity was ≥99%.

[0070] Application Comparative Example 3 Take the reactant epichlorohydrin and the PIL-Br prepared in Comparative Example 1 1.0 A 50 mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner was added in sequence, wherein 5 mmol of epichlorohydrin and 0.03 g of polyionic liquid-porous carbon composite material were added, accounting for 6.5% of the mass content of the reactants; low concentration carbon dioxide (15% CO2, 85% N2) was slowly introduced into the reactor to exclude the residual air inside; then, the reactor oil bath was heated to 100°C, low concentration carbon dioxide was introduced to keep the pressure constant at 1.0 MPa, and the reaction was continued for 13 hours; after the reaction was completed, the reactor was cooled to room temperature in an ice water bath, and the product was quantitatively analyzed by gas chromatography, the yield of propylene carbonate was 35%, and the selectivity was ≥99%.

[0071] Application Comparative Example 4 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 2 and add them into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein 5 mmol of epichlorohydrin and 0.03g of polyionic liquid-porous carbon composite material account for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13 hours; after the reaction is completed, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 72%, and the selectivity is ≥99%.

[0072] Application Comparative Example 5 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 3 and add them into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 58%, and the selectivity is ≥99%.

[0073] Application Comparative Example 6 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 4 and add them into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 74%, and the selectivity is ≥99%.

[0074] Application Comparative Example 7 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 5 and add them into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 66%, and the selectivity is ≥99%.

[0075] Application Comparative Example 8 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 6 and add them in turn into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 70%, and the selectivity is ≥99%.

[0076] Application Comparative Example 9 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 7 and add them into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 45%, and the selectivity is ≥99%.

[0077] Application Comparative Example 10 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 8 and add them in turn into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction is completed, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 62%, and the selectivity is ≥99%.

[0078] Application Comparative Example 11 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 9 and add them into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner in sequence, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 68%, and the selectivity is ≥99%.

[0079] Application Comparative Example 12 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 10 and add them in turn into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction is completed, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 73%, and the selectivity is ≥99%.

[0080] Application Comparative Example 13 Take the reactant epichlorohydrin and the polyionic liquid-porous carbon composite material prepared in Comparative Example 11 and add them in turn into a 50mL stainless steel high-pressure reactor with a polytetrafluoroethylene liner, wherein epichlorohydrin is 5 mmol and the polyionic liquid-porous carbon composite material is 0.03g, accounting for 6.5% of the mass content of the reactants; slowly introduce low concentration carbon dioxide (15% CO2, 85% N2) into the reactor to remove the remaining air inside; then, heat the reactor oil bath to 100°C, introduce low concentration carbon dioxide to keep the pressure constant at 1.0 MPa, and continue the reaction for 13h; after the reaction is completed, cool the reactor to room temperature with an ice-water bath, and the product is quantitatively analyzed by gas chromatography, the yield of propylene carbonate is 70%, and the selectivity is ≥99%.

[0081] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polyionic liquid-porous carbon composite material, characterized in that: The preparation steps are as follows: S1: Mix melamine, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt and zinc acetate dihydrate in proportion at room temperature, and stir at room temperature for 8-12 hours to obtain a liquid organic precursor; S2: thermally decompose the liquid organic precursor at 600-700° C. in an inert gas atmosphere for 2-3 hours, and obtain a Lewis acid-base site-modified porous carbon material through post-treatment; S3: dissolving 1,4-dibromobutane and 1-vinylimidazole in a hydrothermal reactor filled with tetrahydrofuran at a molar ratio of 1:2-2.5, stirring until uniformly mixed at room temperature, reacting at 80-100° C. for 18-24 hours, and after the reaction is completed, post-treating to obtain a white solid 1,4-di(3-vinylimidazole)butane dibromide; S4: The porous carbon material modified with Lewis acid-base sites obtained in S2 is placed in a reaction bottle filled with anhydrous ethanol, subjected to ultrasonic treatment to make it evenly dispersed, and then 1,4-di(3-vinylimidazole)butane dibromide, p-divinylbenzene and 2,2'-azobisisobutyronitrile obtained in S3 are dissolved in anhydrous ethanol in proportion, and added to the anhydrous ethanol solution of the porous carbon material modified with Lewis acid-base sites under stirring, and the mixed solution is reacted at 70-90°C under a nitrogen atmosphere for 16-24 hours, and a polyionic liquid-porous carbon composite material having Lewis acid-base active sites and nucleophilic groups is obtained through post-treatment.

2. The polyionic liquid-porous carbon composite material according to claim 1, characterized in that: The dosage relationship is as follows: the molar ratio of melamine, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and zinc acetate dihydrate in S1 is 1:1:10-15:1-1.3; In S4, the mass ratio of the Lewis acid-base site modified porous carbon material to p-divinylbenzene is 1:0.6-1; the molar ratio of 1,4-di(3-vinylimidazole)butane dibromide, p-divinylbenzene and 2,2'-azobisisobutyronitrile is 5-15:10:

3.

3. The polyionic liquid-porous carbon composite material according to claim 1, characterized in that: The molar ratio of melamine, 2,4,6-tris(4-formylphenoxy)-1,3,5-triazine, 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt and zinc acetate dihydrate in S1 is 1:1:13:1.14; The mass ratio of the Lewis acid-base site modified porous carbon material to p-divinylbenzene in the S4 is 1:0.8, and the molar ratio of 1,4-di(3-vinylimidazole)butane dibromide, p-divinylbenzene and 2,2'-azobisisobutyronitrile is 10:10:

3.

4. The polyionic liquid-porous carbon composite material according to claim 1, characterized in that: The pyrolysis reaction temperature in S2 is 700°C and the pyrolysis reaction time is 2 hours; The heating reaction condition of the mixture in S3 is 90°C for 20 hours; The mixed solution in S4 was heated to react under a nitrogen atmosphere at a temperature of 80° C. for 24 hours.

5. The polyionic liquid-porous carbon composite material according to claim 1, characterized in that: The post-treatment in S2 is to naturally cool to room temperature, wash with deionized water, N,N-dimethylformamide and methanol respectively, and then filter, and vacuum dry the solid to obtain a porous carbon material modified with Lewis acid and base sites; The post-treatment in S3 is to naturally cool to room temperature, and the obtained white solid is filtered, washed with ethyl acetate, and vacuum dried to obtain 1,4-di(3-vinylimidazole)butane dibromide; The post-treatment in S4 is to naturally cool the temperature to room temperature, and the obtained solid is filtered, washed with anhydrous ethanol, and vacuum dried to obtain a polyionic liquid-porous carbon composite material.

6. A method for preparing the polyionic liquid-porous carbon composite material as claimed in any one of claims 1 to 5.

7. Use of the polyionic liquid-porous carbon composite material as described in any one of claims 1 to 5 as a catalyst for the cycloaddition reaction of low-concentration carbon dioxide and epoxide.

8. A method for preparing cyclic carbonate by coupling low-concentration carbon dioxide with epoxide catalyzed by the polyionic liquid-porous carbon composite material according to any one of claims 1 to 5, characterized in that: Using polyionic liquid-porous carbon composite materials as catalysts, low-concentration carbon dioxide and epoxides are reacted through a cycloaddition reaction to synthesize cyclic carbonates.

9. The method for preparing cyclic carbonate by coupling low-concentration carbon dioxide with epoxide catalyzed by the polyionic liquid-porous carbon composite material according to claim 8, characterized in that: The volume concentration of the low concentration carbon dioxide is 10%-25%; The epoxide structural formula is as follows: ; The dosage of the polyionic liquid-porous carbon composite material catalyst is 4%-8% of the mass of the epoxide; the cycloaddition reaction temperature is 70-110° C., the reaction pressure is 0.5-2.5 MPa, and the reaction time is 8-16 hours.

10. The method for preparing cyclic carbonate by coupling low-concentration carbon dioxide with epoxide catalyzed by the polyionic liquid-porous carbon composite material according to claim 8, characterized in that The volume concentration of the low concentration carbon dioxide is 15%; The cycloaddition reaction temperature is 100° C., the reaction pressure is 1 MPa, and the reaction time is 13 hours.

Citation Information

Cited By

  • Cyclic carbonate for electrolyte, preparation method of cyclic carbonate and electrolyte

    CN120289415A

  • Preparation method and application of polyion liquid / alumina aerogel composite material

    CN121016844A